Directions for the implementation of foreign experience in operative and investigative counteraction to intentional murders by criminal police units (on the example of Canada and the USA) (Law and Safety, 2022)
Recently, scientific interest in the study of foreign experience in combating criminal illegality among domestic scientists is constantly growing, which indicates an effort to investigate the best preventive practices of separate countries and the search for ways of their implementation in Ukraine. However, with regard to the direct study of the foreign experience of operative and investigative countermeasures against intentional murders by police units of various foreign countries, there is a lack of such studies today, which increases the relevance of the chosen direction and gives prospects for determining effective practices using a targeted approach to combating deliberate murders and defining such a model of operative and investigative activity. The choice of an appropriate strategy by a particular state and the formation of an appropriate preventive program or a program to combat criminal wrongdoing is determined not only by the current criminogenic situation in this country and in the world in general, but also by the relevant historical, cultural and religious traditions. When considering the specifics of combating criminal wrongdoing in a particular country, it is necessary to take into account the country's membership of the corresponding criminological system. Modern criminology distinguishes Anglo-American, Western European, East Asian, socialist, Muslim and mixed criminological systems.The reforms that have been taking place in Ukraine recently require restructuring and a significant increase in the level of efficiency and quality of law enforcement agencies. First of all, these requirements apply to operational units, patrol police and community police officers. Successful implementation of the tasks assigned to these divisions is impossible without taking into account the best examples of the experience of countries such as Canada and the USA. The purpose of the article is to analyze the international experience of operational and investigative prevention of intentional homicides by criminal police units, as well as legislation that provides for the development of an effective system of prevention of intentional homicides in Ukraine. The task of the research is the analysis of various programs to combat intentional homicides that operate in different countries of the world, as well as the international experience of operative and investigative prevention of intentional homicides, which can become the basis for the development of appropriate Ukrainian legislation in this area. The positive international experience of operative and investigative prevention of intentional murders is analyzed. The experience of the USA in combating criminal wrongdoing, in particular intentional murders, is considered, and three models of preventive activity are distinguished and analyzed: the model of social institutions, the model of individual safety, and the model of influence through the environment. It was concluded that conducting a comparative analysis of the prevention of intentional homicides in different countries is the basis for the development of the most promising directions for improving domestic legislation in this area.
Keywords: prevention of murders; combating murders; crime prevention; criminal police units; international experience.